Liver Cirrhosis: Pathophysiology, Diagnosis, and Management - Baiq Nadya Putri Maharani; Aulia Dwi Hendriani; Putu Wika Pramesti Iswari (Jurnal Biologi Tropis, 2023)
Liver disease is still a concern in world health and liver cirrhosis is the eleventh leading cause of death in the world. Cirrhosis caused 1.32 million deaths in 2017. Liver cirrhosis is a fibrosis or nodule formation in the liver. The study was conducted on databases, such as PubMed, google scholar and gray literature. With inclusion criteria, that are free full text publications published in 2015-2022 and having relevant discussions. Fibrosis in cirrhosis of liver begins with the activation of Stellate and Kupffer cells, damaged hepatocytes and activated platelets are also invoved. Inflammatory cells will appear as a result of the damage and cause fibrosis due to the secretion of cytokines. In addition, there are pathological features, namely nodule regeneration and loss of normal lobular architecture within the nodule. The patient's diagnosis start from anamnesis to gather information related to risk factors, physical examination, laboratory tests, imaging, liver biopsy if necessary. Management can be carried out according from etiology of the cause of liver cirrhosis. Complications of liver cirrhosis are portal hypertension, ascites, hepatic encephalopathy, hepatocellular carcinoma, hyponatremia, and acute kidney injury. Liver cirrhosis is a liver fibrosis caused by Stellate, Kupffer cells, damaged hepatocytes, and activated platelets. Inflammatory cells cause fibrosis, leading to regenerating nodules and decreased blood flow. Diagnosis involves anamnesis, physical examination, laboratory tests, imaging, and liver biopsy if needed. Treatment is based on the etiology of liver cirrhosis, with complications including portal hypertension, ascites, and hepatic encephalopathy.